Impact of constructs of quality of work life in relation to women laborers under mahatma gandhi national rural employment guarantee act( mgnrega): an analytical study - Pandey, Archana; B.K, Jha (Journal of Management and Science, 2012)
Human resource is one of the fundamental factors influencing the development of a nation. The socio-economic and political position of a nation is very much dependent on how it recruits, motivates and retains its workforce? In present scenario it is very essential to keep in mind the importance of Quality of Work Life for employees while drafting the various national schemes which intend to provide quality of life to people. This is because QWL is an integral part of quality of life. The present study aims at identifying the various constructs of QWL responsible in affecting the QWL of employees particularly in the case of women workers in rural area. The constructs of QWL discussed in the present study include safe work environment, equitable wages, equal employment opportunities and opportunities for advancement. (Mirvis and Lawler,1984). The whole study has been framed from the perspective of women workers employed under MGNREGA. Further, the study attempts to find out how far they have been taken into consideration by the policy drafters of MGNREGA particularly for women employees and suggests the measures for improving QWL among MGNREGA employees particularly in the case of women. The study concludes that the important constructs of QWL have been taken into consideration while drafting MGNREGA but there is still much that must be done to strengthen womens‟ situation in rural areas .The suggestions for the same have been enumerated and the implications of the study discussed.